Thrombosed aneurysm of saphenous vein coronary artery bypass grafting - Queiroz,Rodolfo Mendes (2017)
Summary We describe the case of a male patient, aged 76 years, referred for cardiac investigation due to retrosternal chest pain and dyspnea. He had a history of acute myocardial infarction and angioplasties in the last 30 years, including a saphenous vein coronary artery bypass grafting (SVCABG). Echocardiogram showed hypoechoic oval formation near the right ventricle, suggesting a pericardial cyst. Computed angiotomography revealed a predominantly fusiform and thrombosed aneurysmal dilation of the SVCABG to the right coronary artery. SVCABG aneurysms are very rare and potentially fatal. They usually appear in the late postoperative period, and patients are often asymptomatic. On radiography, it is frequently presented as enlargement of the mediastinum, with echocardiography, computed tomography and magnetic resonance imaging being very useful for diagnosis. Coronary angiography is the gold standard to detect these cases. Our report illustrates a rare situation arising late from a relatively common surgery. Due to its severity, proper recognition in the routine assessment of patients with a similar history is essential.